Investigating The Adoption of Knowledge Management in a Non-Govermental Organization in Malaysia - Kalid, Khairul Shafee; Saide, Saide (2018)
Non-governmental organizations use knowledge extensively in humanitarian efforts, engagements with organizations concerning the welfare of the people and other activities. The knowledge in nongovernmental organizations are mostly tacit. Nevertheless, little is known about knowledge management practices in non-governmental organizations.The aim of this study is to investigate the adoption of knowledge management in a nongovernmental organization.This study adopts a case study research design. Data was collected through a survey sent to a non-governmental organization.The questionnaire was based on the four pillars of knowledge management namely management and organization, people and culture, content and processes and infrastructure. A total of 31 respondents from one NGO participated in the survey.The data was analyzed using descriptive analyses.The findings indicate that knowledge is widely acknowledge as important in non-governmental organizations.To a certain extent, knowledge management principles have been practiced in the organization.However, non-governmental organizations have yet to establish an organization wide knowledge management strategy.The study provides an understanding of how knowledge management is perceived by the non-governmental organizations and provide valuable insights to the practice of knowledge management in nongovernmental organizations.